Control of shock wave/boundary layer interaction induced by the microjet configuration. (December 2022) - Xu, Hao; Huang, Wei; Yan, Li; Du, Zhao-bo
Abstract: Shock wave/boundary layer interaction (SBLWI) is a common coupling phenomenon that occurs in hypersonic vehicles, and it adversely affects the flow fields inside and outside the vehicle. Currently, the microjet active flow control approach has been extensively investigated experimentally. Herein, the influence of the microjet hole type on SBLWI control is investigated and the flow field structures of the microjet in the near field are obtained. Additionally, the control effects of isosceles triangular microjet holes with different vertex angles are compared with those of circular and square microjet holes. The numerical results show that the control effect of the microjet on SBLWI gradually improves with increasing triangular vertex angle, and the control effect of the triangular microjet hole with a large vertex angle is better than that of circular and square microjet holes. In all working conditions, the triangular microjet hole with a 90° vertex angle that is placed along the flow direction affords the best control effect, and it can reduce the volume of the separation zone at the corner by 74.96%. Simultaneously, the addition of the microjet causes some loss of the total pressure, but the value is small. Graphical abstract: Image 1 Highlights: Influence of the microjet hole type on SBLWI control is investigated. Control effects of isosceles triangular microjet holes with different vertex angles are compared. Control effect of the microjet on SBLWI gradually improves with increasing triangular vertex angle. Triangular microjet hole with a 90° vertex angle reduces the volume of the separation zone by 74.96%.